Global guidance for the recognition, diagnosis, and management of tumor‐induced osteomalacia. (13th December 2022) - Jan de Beur, Suzanne M.; Minisola, Salvatore; Xia, Wei‐bo; Abrahamsen, Bo; Body, Jean‐Jacques; Brandi, Maria Luisa; Clifton‐Bligh, Roderick; Collins, Michael; Florenzano, Pablo; Houillier, Pascal; Imanishi, Yasuo; Imel, Erik A.; et al.
Abstract: Tumor‐induced osteomalacia (TIO) is a rare paraneoplastic syndrome caused by mesenchymal tumors that secrete fibroblast growth factor 23 (FGF23). Patients present with progressive bone pain, muscle weakness, and fragility fractures. TIO is characterized by hypophosphatemia, excess renal phosphate excretion, and low/inappropriately normal 1, 25‐dihydroxyvitamin D (1, 25(OH)2 D) levels. Rarity and enigmatic clinical presentation of TIO contribute to limited awareness among the medical community. Accordingly, appropriate diagnostic tests may not be requested, leading to delayed diagnosis and poorer patient outcomes. We have developed a global guidance document to improve the knowledge of TIO in the medical community, enabling the recognition of patients with TIO and appropriate referral. We provide recommendations aiding diagnosis, referral, and treatment, helping promote a global standard of patient management. We reviewed the literature and conducted a three‐round Delphi survey of TIO experts. Statements were drafted based on published evidence and expert opinions (≥70% consensus required for final recommendations). Serum phosphate should be measured in patients presenting with chronic muscle pain or weakness, fragility fractures, or bone pain. Physical examination should establish features of myopathy and identify masses that could be causative tumors. Priority laboratory evaluations should include urine/serum phosphate and creatinine to assess renal tubular reabsorption of phosphate and TmP/GFR, alkaline phosphatase, parathyroid hormone, 25‐hydroxyvitamin D, 1, 25(OH)2 D, and FGF23. Patients with the clinical/biochemical suspicion of TIO should be referred to a specialist for diagnosis confirmation, and functional imaging should be used to localize causative tumor(s). Recommended treatment is tumor resection or, with unresectable/unidentifiable tumors, phosphate salts plus active vitamin D, or burosumab. Abstract :